Work engagement pada anggota Satuan Polisi Pamong Praja: Bagaimana peranan safety climate dan kontrak psikologis? - Ella Dwi Sartika; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between safety climate and psychological contract with work engagement among members of the Civil Service Police Unit in Gresik Regency. The design of this study used correlational quantitative with a number of 94 members of the Daily Freelancers of the Civil Service Police Unit, Gresik Regency. The data collection method was carried out through distributing questionnaires using a Likert scale. The data obtained were then analyzed using multiple linear regression with the help of SPSS 25.0 for Windows. The results obtained simultaneously show a coefficient value of 98.302 with significance = 0.000 <0.01, which means that there is a positive relationship between safety climate and psychological contract with work engagement. This shows that the higher the safety climate and the psychological contract on members, the higher the work engagement. The effective contribution to the safety climate is 27.5% and the psychological contract is 40.9%, while 31.6% work engagement is influenced by other predictors. Keywords: Psychological Contract, Safety Climate, Work Engagement